In-field dependences of the critical current density Jc in GdBa2Cu3O7-d coated conductors produced by Zr irradiation and post-annealing at low temperatures. (February 2019) - Haberkorn, N.; Suárez, S.; Lee, Jae-Hun; Moon, S.H.; Lee, Hunju
Abstract: We report the influence of 6 MeV Zr 4+ irradiation and post-irradiation annealing (200 °C) in the in-field dependences of the critical current densities J c of 1.3 thick GdBa2 Cu3 O7-d coated conductors grown by co-evaporation. Samples were irradiated with 6 MeV Zr 4+ and fluences between 2.3 × 10 11 cm −2 and 3 × 10 12 cm −2 . The correlation between the superconducting critical temperature T c and in-field dependences of J c has been analyzed. In addition, random disorder introduced by irradiation was reduced by thermal annealed at 200 °C. The analysis of our experimental findings indicates that the optimal irradiation (reducing random disorder by annealing) results in the suppression of the self-field J c of ≈10% and in-field J c enhancements nearly doubled at about 5 T. A clear correlation between T c, disorder and self-field J c is observed. Additional random disorder and nanoclusters suppress systematically T c and increase the flux creep relaxation at intermediate temperatures (reducing the characteristic glassy μ value). Highlights: GdBa2 Cu3 O7 coated conductors are irradiated with 6 MeV Zirconium. The in-field dependences of J c are improved withH parallel to the c-axis. Reduction of random disorder by thermal annealing improves the J c at low magnetic fields. Characteristic glassy exponents are analyzed.